PENGARUH ENTERPRISE RISK MANAGEMENT DAN LAVERAGE TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING - Siska Dewi; Kusuma Wijaya; Fangela Myas Sari (JURNAL ILMIAH EDUNOMIKA, 2026)
This study examines the effect of Enterprise Risk Management (ERM) and leverage on firm value with financial performance as the intervening variable. The data used is quantitative data from the annual report which can be obtained through the idx.co.id website and the official website of each company entity. The population in this study is the property and real estate sector which is listed on the IDX 2018 – 2021. Sampling using purposive sampling and obtained a sample of 10 companies. Analysis technique with multiple linear regression analysis and sobel test. The result is that ERM has no effect on financial performance. Leverage has a negative effect on the company's financial performance. ERM has a positive effect on firm value. Leverage has no positive effect on firm value. ERM has no effect on corporate value through financial performance. Leverage affects the value of the company through financial performance. The novelty of this study is that it involves financial performance as a mediating variable to measure ERM and leverage on firm value. The limitations of the research are the research sample, the measurement of variables only uses one ratio, besides that only the sobel test analysis is used. Keywords: Enterprise Risk Management, Leverage, Financial Performance and Company Value